Penerapan Model Pembelajaran STAD Untuk Meningkatkan Hasil Belajar Siswa Kelas X Madrasah Aliyah Negeri 2 Halmahera Utara - Tri Wulandari Ilham; Irawati F Tomagola (EDUKASI, 2023)
This study aims to determine the implementation of the STAD learning model in increasing student learning activities in each cycle, and to determine student learning outcomes in class X IPA 2 Madrasah Aliyah Negeri 2 Halmahera Utara. The research method used is Classroom Action Research (CAR). This research was conducted in 2 cycles, each cycle consisting of planning, action, observation, and reflection. The subject of this research was conducted in class X IPA 2 Madrasah Aliyah Negeri 2 Halmahera Utara, totaling 17 students. The approach used in this research is a descriptive approach. Data collection techniques using instruments in the form of observation sheets and tests. The results showed that learning outcomes using the STAD learning model increased and the achievement of student learning outcomes increased to 70% in cycle II and was categorized as successful. Teacher and student activity in the learning process has also increased with a percentage of teacher activity of 100%. Meanwhile, student activity increased by 86.27% in cycle II.